Alpha‐1 antitrypsin therapy is safe and well tolerated in children and adolescents with recent onset type 1 diabetes mellitus1. Issue 5 (15th June 2015) - Rachmiel, Marianna; Strauss, Pnina; Dror, Nitzan; Benzaquen, Hadassa; Horesh, Orit; Tov, Nave; Weintrob, Naomi; Landau, Zohar; Ben‐Ami, Michal; Haim, Alon; Phillip, Moshe; Bistritzer, Tzvi; et al.
Abstract : Background and objectives: Alpha‐1 antitrypsin (AAT) has been shown to reduce pro‐inflammatory markers and protect pancreatic islets from autoimmune responses in recent studies. Our aim was to evaluate its safety and tolerability in three different doses, in a pediatric population with recent onset type 1 diabetes mellitus (T1DM). Methods: A 37‐wk prospective, open‐label, phase I/II interventional trial, comprised of 24 recently diagnosed subjects (12 males; age 12.9 ± 2.4 yr), who received 18 infusions of 40, 60, or 80 mg/kg/dose high‐purity, liquid, ready to use AAT over 28 wk (Glassia ® ; Kamada Ltd., Ness Ziona, Israel). Primary outcomes: safety and tolerability; secondary outcomes: glycemic control, C‐peptide reserve, and autoantibody levels. Possible responders were defined as individuals with peak C‐peptide that declined less than 7.5% below baseline. Results: No serious adverse events, diabetic ketoacidosis (DKA), or severe hypoglycemic episodes were reported. Adverse events were dose‐independent and transient. Glycemic control parameters improved during the study in all groups, independent of dosage. Hemoglobin A1c (HbA1c) decreased from 8.43 to 7.09% (mean, p < 0.001). At the end of the study, 18 subjects (75%) had a peak C‐peptide ≥0.2 pmol/mL. Eight subjects (33.3%) were considered possible responders and were characterized by shorter duration of T1DM at screening (54.5 ± 34.3 vs. 95.9 ± 45.7 d, p = 0.036) and greater decrease in their HbA1c during the study period (−2.94 ± 1.55 vs.−0.95 ± 1.83%, p = 0.016). Conclusions: AAT treatment was safe and well tolerated in pediatric subjects with recently diagnosed autoimmune diabetes. Placebo‐controlled studies with larger cohorts and dose range are warranted in order to assess efficacy in maintaining pancreatic beta cell reserve and glycemic control.